Analisa Kelayakan Finansial Usaha Internet Wireles pada Multinet Aircom Muara Bulian - Muryati Muryati; Kasyati Yunita W (Universitas Batanghari Jambi, 2019)
This research aims to analyze the financial feasibility of Wireles Internet at Multinet Aircom Muara Bulian in Muara Bulian. Using the analysis of investment criteria Net Present Value (NPV), Net B/C Ratio, Internal Rate Of Return (IRR) and Payback Pariod. Results of the calculation of Internet business eligibility criteria wireles on Multinet Aircom in Muara Bulian obtained the calculation result of Net Present Value (NPV) of Rp. 106,357,720,-indicating that the Internet business investment wireles on Multinet Aircom in Muara Bulian give a profit of Rp. 106,357,720,-results Net Benefit Cost Ratio (Net B/C) obtained by 2.1 > 1, this indicates that for each current value of the expenditure of Rp. 1,-will provide benefits amounting to Rp. 2.1. The result of Internal Rte Of Return (IRR) calculation obtained by 22% greater than the prevailing interest rate of 12% it shows that wireles internet business is feasible to run because IRR is greater than the prevailing bank interest rate. The result of calculation of return on investment (Payback Pariod) in Internet business Wireles indicates that the business is gaining a return on investment for 2 years 9 months 28 days means in that period the cost of investment incurred can be returned, so the faster the period of refund of investment costs, then the effort is carried out better.